Effects of the Chinese herbal medicine Hong Huang decoction, on myocardial injury in breast cancer patients who underwent anthracycline-based chemotherapy - Cao, Sihan; Xue, Jingxian; Chen, Lu; Hao, Yun; Lu, Meijuan; Feng, Ming; Wang, Huanhuan; Zhou, Jun; Yao, Chang (Frontiers in Cardiovascular Medicine, 2022)
.OBJECTIVE: To assess the effects of Hong Huang Decoction (HHD), a Chinese herbal medicine, on myocardial injury in breast cancer patients who underwent anthracycline (ANT)-based chemotherapy. METHODS: A total of 51 patients with breast cancer who underwent an ANT-based chemotherapy program and met the inclusion/exclusion criteria were allocated to the treatment or placebo groups using a random number generation process. Patients in the treatment group received liquid HHD twice a day. Treatment was given from one day prior to chemotherapy up to the end of chemotherapy (after 6 months). Participants in the placebo group received a placebo over the same schedule. Left ventricular ejection fraction (LVEF), global longitudinal strain (GLS), diagnostic markers of acute myocardial infarction (e.g. lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB) and B-type natriuretic peptide (BNP)), nitric oxide (NO), superoxide dismutase (SOD), as well as pro-inflammatory cytokines (e.g. tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and human C-reactive protein (CRP)), and anti-inflammatory cytokine interleukin-10 (IL-10), were outcome measures assessed before chemotherapy, 3 months and 6 months after chemotherapy. RESULTS: Compared to the placebo group, the GLS value was significantly higher in the treatment group (19.95 ± 1.16 vs. 19.06 ± 1.64, P ≤ 0.001). Significant differences were also noted for levels of SOD (689.71 ± 203.60 vs. 807.88 ± 182.10, P < 0.05), IL-6 (58.04 ± 22.06 vs. 194.20 ± 40.14, P ≤ 0.001), IL-10 (237.90 ± 94.98 vs. 68.81 ± 32.92, P ≤ 0.001), NO (75.05 ± 26.39 vs. 55.83 ± 19.37, P ≤ 0.005), and TNF-α (301.80 ± 134.20 vs. 680.30 ± 199.60, P ≤ 0.001) in the patients before chemotherapy compared to 6 months after initiating chemotherapy. CONCLUSION: HHD regulated the levels of IL-6, IL-10, SOD, NO, and TNF-α. The results demonstrated that GLS is a better indicator of early myocardial injury compared to LVEF, and HHD could modulate oxidative stress to protect against ANT cardio toxicity. Keywords: breast cancer, chemotherapy, anthracycline, Hong Huang Decoction, GLS